2011
DOI: 10.1111/j.1471-4159.2011.07532.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel glycogen synthase kinase‐3 inhibitor 2‐methyl‐5‐(3‐{4‐[(S )‐methylsulfinyl]phenyl}‐1‐benzofuran‐5‐yl)‐1,3,4‐oxadiazole decreases tau phosphorylation and ameliorates cognitive deficits in a transgenic model of Alzheimer’s disease

Abstract: Alzheimer's disease (AD) is a neurodegenerative disorder characterized by a progressive deterioration in cognitive function and memory and has two pathological hallmark lesions: senile plaques and neurofibrillary tangles (NFTs). These pathological features are comprised of the small AbstractAlzheimer's disease (AD) is a neurodegenerative disorder leading to a progressive loss of cognitive function and is pathologically characterized by senile plaques and neurofibrillary tangles. Glycogen synthase kinase-3 (GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 50 publications
0
56
0
Order By: Relevance
“…Indeed, an orally administrable-related oxidiazole, 2-methyl-5-(3-{4-[(S)-methylsulfinyl]phenyl}-1-benzofuran-5-yl)-1,3,4-oxadiazole (MMBO), was recently shown to decrease hippocampal Tau phosphorylation at GSK-3 sites, but without affecting Ab pathology, in the 3xTg transgenic AD mouse model. In behavioral assessments, MMBO significantly improved memory deficits in the Y-maze and novel object recognition tests (Onishi et al, 2011). Therefore, these molecules appeared effective in preclinical tests.…”
Section: A Gsk-3b Inhibitor Alleviates Ab 25-35 -Induced Toxicity Andmentioning
confidence: 91%
“…Indeed, an orally administrable-related oxidiazole, 2-methyl-5-(3-{4-[(S)-methylsulfinyl]phenyl}-1-benzofuran-5-yl)-1,3,4-oxadiazole (MMBO), was recently shown to decrease hippocampal Tau phosphorylation at GSK-3 sites, but without affecting Ab pathology, in the 3xTg transgenic AD mouse model. In behavioral assessments, MMBO significantly improved memory deficits in the Y-maze and novel object recognition tests (Onishi et al, 2011). Therefore, these molecules appeared effective in preclinical tests.…”
Section: A Gsk-3b Inhibitor Alleviates Ab 25-35 -Induced Toxicity Andmentioning
confidence: 91%
“…By contrast, the trial in amnestic mild cognitive impairment suggested that lithium treatment was associated with a decrease in p-tau in the CSF and better cognitive performance. Another GSK inhibitor, 2-methyl-5-(3-{4-[(S)-methylsulfinyl] phenyl}-1-benzofuran-5-yl)-1,3,4-oxadiazole, reduces hippocampal tau phosphorylation at GSK-3 sites and ameliorates behavioural dysfunction in 3×Tg-AD mice 70. The non-specific tau kinase inhibitor K252a (for CDK5, GSK3 and ERK1) also reduced levels of hyperphosphorylated tau and ameliorated the motor phenotype in P301L mutant tau Tg mice (JNPL3) 71.…”
Section: Therapeutic Strategies For Tau Mediated Neurodegenerationmentioning
confidence: 99%
“…However, the mice did not live longer. 2-Methyl-5-(3-{4-[(S)-methylsulfinyl]phenyl}-1-benzofuran-5-yl)-1,3,4-oxadiazole, another novel GSK-3 inhibitor, has recently been reported to produce a similar positive outcome in vitro and in a mouse model (Onishi et al, 2011). Successfully targeting GSK-3, now a goal in many disease fields, is evidently a complex undertaking.…”
Section: F Glycogen Synthase Kinase-3 Antagonistsmentioning
confidence: 99%
“…Surprisingly, A␤ plaque removal was the only mechanism considered by these authors, despite the doubt cast on the utility of this endpoint by the AD patient trial of AN1792 (A␤42; Elan Pharmaceuticals, South San Francisco, CA) several years ago (Holmes et al, 2008). It is useful to recall, when interpreting Onishi et al, 2011 this bexarotene data, that anti-TNF treatment produces a very similar outcome in the same mouse model (Shi et al, 2011), and an apoE mimetic has since done so in a related mouse strain (Vitek et al, 2012). Literature exists on the side effects of bexarotene, but whether these arise from high apoE or other consequences of retinoid X receptor activation has yet to be determined.…”
Section: H Apolipoprotein E Mimetics and Bexarotenementioning
confidence: 99%